(untitled) (American Journal of Islam and Society, 1987)
Introduction This paper seeks to define human resources development (HRD) as a necessary, if not a sufficient, tool for bringing about societal change in less developed countries (LDC‘s), and reflects upon different concepts of ”develop ment,” including the Islamic view of it. Then, it reviews the status of education in the Muslim World and moves on to describe the TALIM model of HRD. In the end, a few salient features of the mechanism of this model are suggested. Also, an HRD policy plan that needs to be implemented by the Muslim Ummah is included as an appendix. Human Resources Development (HRD) It can be easily argued that HRD has been an established tradition since time immemorial, as it is difficult to determine when individual apprenticeship started. The well-developed ancient civilizations of China, India, Mesopotamia and Egypt would have been impossible without an established tradition of apprenticeship. In the West, however, HRD as an organized activity does not have a long history. Here they have only recently begun to realize its significance. The West has now started to move from the stage of treating labor as a disposable element of production to a position where “human factor” is considered significant as both the planner and the beneficiary of the fruits of production. According to Knowles (1960) and Nadler (1970), HRD is a strategy of developing skilled manpower. Nadler (1mO) defines HRD as a series of organized activities, conducted within a specified time, and designed to produce behavioral change. According to him, it has four components: (1) employee training, (2) employee education, (3) employee development, and (4) nonemployee development ...